Разработка технологического процесса восстановления поверхности деталей из высокоуглеродистой легированной стали - Романюк, Светлана Павловна (Национальный технический универститет "Харьковский политехнический институт", 2019)
Рассмотрена технология восстановления деталей наплавкой. В качестве модификатора восстановительных покрытий использовали немагнитную составляющую детонационной шихты, полученную от утилизации боеприпасов. Для анализа степени эффективности предложенной технологии сопоставительно проведены комплексные исследования и оценено влияние состава электрода, используемого модификатора на качество сварного шва, переходной зоны, а также структуру металла восстановленного покрытия. Показано, что лучшие результаты достигнуты при обмазке модифицирующей шихтой электрода Т590. Максимальная микротвердость при нагрузке 0,245 N составила 1498,3 МПа. Это обеспечивает повышение износостойкости модифицированного наплавленного слоя на 17 %.

The technology of restoring by surfacing parts from high-carbon alloy steel is considered. The non-magnetic component of the detonation charge obtained from the disposal of ammunition was used as a modifier of recovery coatings. To analyze the degree of effectiveness of the proposed technology, comprehensive studies were carried out using optical and electron microscopy, X-ray spectral analysis, and microhardness assessment. A comparative study was made of the influence of the composition of the electrode and the used modifier from recycled materials on the quality of the weld, transition zone, and also the metal structure of the reduced coating. It is shown that cracks are formed when surfacing with the TsL11 electrode without a modifier; when using ANO-21, zones with a significant drop in microhardness are present. The features of the distribution of components during surfacing were studied, and stability studies of the properties of the reduced layer with the introduction of a charge were carried out. It was shown that the modifying additive is distributed not only in the deposited layer, but also in the transition layer. The use of additives 2-3 times reduces the width of the transition layer, contributes to greater adhesion. The best results were achieved when coated with a modifying mixture of the T590 electrode. The maximum microhardness at a load of 0.245N was 1498.3 MPa. This provides an increase in wear resistance of the modified deposited layer by 17%.
Development of technological process for restoring the surface of toоls made of high-carbon alloy steel
Keywords: электродуговая наплавка; модифицирование; детонационная шихта; electric arc surfacing; modification; detonation charge